The association between perceived student gratitude and teacher family role performance: A moderated mediation model - Shaoqing Su; Yifan Ou; Ying Liao (Acta Psychologica)
Objective: In recent years, numerous studies have highlighted the positive impact of student gratitude on individual development. However, a significant gap remains in the literature concerning how student gratitude influences teachers' family behavioral performance in their daily lives. This paper introduces Conservation of Resources (COR) Theory to examine the mediating effect of work-family enrichment on the relationship between student gratitude and teachers' family role performance, while also investigating whether intrinsic motivation moderates this relationship. Methods: In this study, data were collected from a sample of 1, 068 teachers and their spouses involved in student management and teaching activities across 21 colleges and universities in northwestern and southeastern China, utilizing a two-wave time-lagged method. The assessment of college teachers was conducted using the gratitude scale, family role performance scale, work-family enrichment scale, and intrinsic motivation scale. To investigate the moderated mediation effects, SPSS 26. 0 and Amos 24. 0 statistical software were employed for data analysis and hypothesis testing. Results: Perceived student gratitudesignificantly predicts teacher’ s family role performance. Work-family enrichment serves as a mediator in the relationship between perceived student gratitude and teachers' family role performance. Addditionaly, intrinsic motivation moderates both the relationship between perceived student gratitude and work-family enrichment, as well as the indirect effect of perceived student gratitude on teachers' family role performance through the mediation of work-family enrichment. Conclusion: This study enhances our understanding of how perceived student gratitude impacts teachers' family role performance, enriches our knowledge of the role of intrinsic motivation in this context, and broadens the antecedent research related to Conservation of Resources (COR) theory. The findings underscore the importance for administrators of higher education institutions to emphasize and promote the expression of perceived student gratitude. Furthermore, universities and colleges should also consider the family needs of teachers when facilitating the realization of their intrinsic motivation, thereby enabling teachers to achieve a better balance between their professional and family lives.